2021
DOI: 10.1177/00031348211047497
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Visits to a Pediatric Emergency Department During the COVID-19 Quarantine and “Stay at Home” Period

Abstract: Background Impact of social distancing on pediatric injuries is unknown. Methods We retrospectively compared injury visits to a pediatric emergency department by individuals ≤21 years during “Stay at Home” (SHO) period to the same period in 2019 (non-SHO). Demographics, types, and outcomes of injuries were noted. Results Although, there was a 35.6% reduction in trauma-related emergency department visits during SHO period (1226 vs 1904), the proportion of injury visits increased (15.5% vs 8.1%, P < .001) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 27 publications
1
29
1
Order By: Relevance
“…Our study brings to light multiple significant findings related to the effects of the COVID-19 pandemic on pediatric firearm injuries. Consistent with multiple previous studies [ 8 , [11] , [12] , [13] , [14] , [15] , [16] ], pediatric firearm injury rates were found to have significantly increased during the pandemic compared to the five preceding years. While most previous studies on the topic do not include information on the intent or circumstances surrounding the shootings [ 8 , 11 , 12 , 14 , 16 ], we found that the escalation in pediatric firearm injuries was driven by a significant increase in pediatric firearm assaults/homicides.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our study brings to light multiple significant findings related to the effects of the COVID-19 pandemic on pediatric firearm injuries. Consistent with multiple previous studies [ 8 , [11] , [12] , [13] , [14] , [15] , [16] ], pediatric firearm injury rates were found to have significantly increased during the pandemic compared to the five preceding years. While most previous studies on the topic do not include information on the intent or circumstances surrounding the shootings [ 8 , 11 , 12 , 14 , 16 ], we found that the escalation in pediatric firearm injuries was driven by a significant increase in pediatric firearm assaults/homicides.…”
Section: Discussionsupporting
confidence: 90%
“…The relative decrease in unintentional pediatric firearm injuries that we discovered during the pandemic contradicts this theory, though the risks for firearm injury they point out are likely still accurate and significant. Our finding that pediatric firearm assaults/homicides significantly increased is likely still related in part to increased gun purchasing [ 8 , 11 , 13 , [23] , [24] , [25] ] and decreased youth supervision [ 8 , 14 , 16 ] associated with the COVID-19 pandemic. However, other factors such as COVID-19-induced economic crisis and subsequently increased neighborhood violence/crime rates may have played a more significant role in elevating pediatric firearm assaults/homicides.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations